Analisis Formulasi dan Mutu Gizi Barongko “BAGOBEAN” Berbasis Pangan Lokal sebagai Strategi Intervensi Makanan Tambahan bagi Balita Wasting - Zafira Ananda Neda; Theresia Puspita; Hasan Aroni (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Wasting is a form of acute malnutrition commonly found in toddlers, characterized by weight that is not proportional to height. In 2024, the prevalence of wasting among toddlers in Indonesia reached 6.2%. This condition is influenced by various factors, both direct and indirect. Thus study aims to analyze the formulation of kepok bananas, purple sweet potatoes, and mung beans in barongko products as snack for toodlers with wasting. Thus study applied a quantitative experimental study using a completely randomized design (CRD) with one factor, namely the formulation of raw materials with three levels of treatment. Each treatment was tested to determine nutritional quality (energy, protein, fat, and carbohydrates), protein quality, organoleptic quality, and the best treatment. The result showed 1) Variations in the proportions of kepok bananas, purple sweet potatoes, and mung beans affect the energy, protein, and carbohydrate content. Treatment F3 showed the highest nutritional value, namely energy 282.76 kcal; protein 7.74 g; fat 15.33 g; and carbohydrates 31.02 g. 2) The formulation of ingredients affects organoleptic quality. Treatment F3 obtained the highest score (color 3.87; taste 3.67; aroma 3.8; texture 3.73). 3) The effectiveness index shows that the best treatment is F3 with a ratio of plantain : purple sweet potato : mung beans = 20 : 50 : 30, with a total effectiveness value of 0.974. The conclusion of thi study is the best treatment in developing a barongko formulation based on local foods is F3.